Changes in Kidney Functions during Middle-distance Triathlon in Male Athletes - Poortmans, J. R.; Jeannaud, F.; Baudry, S.; Carpentier, A. (International Journal of Sports Medicine, 2015)
Strenuous exercise induces proteinuria which is related to the intensity of exercise. However, renal responses to each type of exercise during a middle-distance triathlon have not been reported. The present study, carried out on 7 healthy athletes, investigated renal function at rest and after each exercise of a half-triathlon race. Blood and urine samples were collected at rest and after each specific event. Protein excretion and renal clearances were determined on each sample. Compared with resting values, albuminuria was increased by a factor of 30 (p<0.05) after swimming but did not differ from the resting value after cycling and running (p>0.05). Rates of β2-microglobulin and retinol-binding protein excretion did not change throughout the triathlon (p>0.05). Glomerular filtration rate (expressed as creatinine clearance) remained stable after each exercise event, whereas tubular reabsorption rate (expressed as urea clearance) was reduced by 50, 40 and 65% after swimming, cycling and running, respectively, compared to pre-exercise values (p<0.05). Glomerular membrane permeability (expressed as albumin clearance) was significantly increased by the swimming event (13 times, p<0.05). These results suggest that middle-distance triathlon has a noticeable impact on the glomerular membrane permeability (albumin clearance) and elimination of protein waste (urea clearance) depending on exercise type.
Keywords: middle-distance triathlon; proteinuria; kidney filtration; glomerular permeability; tubular reabsorption